Technical modifications and outcomes after Associating Liver Partition and Portal Vein Ligation for Staged Hepatectomy (ALPPS) for primary liver malignancies: A systematic review. (June 2020) - Baili, Efstratia; Tsilimigras, Diamantis I.; Moris, Dimitrios; Sahara, Kota; Pawlik, Timothy M.
Abstract: Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) represents a novel surgical technique which provides rapid and effective liver regeneration allowing for the resection of lesions initially deemed unresectable. The objective of this systematic review is to summarize all technical modifications of the original ALPPS approach (mALPPS) for primary liver malignancies and evaluate short- and long-term outcomes. A systematic search of the literature was conducted using PubMed, Scopus, Cochrane Library Central, Google Scholar, and clinicaltrials.gov databases until July, 31 2019. The following keywords were utilized: "Associating Liver Partition and Portal Vein Ligation for Staged hepatectomy", "ALPPS", "Portal Vein Embolization (PVE) And In Situ Split", "Portal Vein Ligation (PVL) And In Situ Split". A total of 24 studies were identified incorporating data on 83 patients who underwent a mALPPS for a primary liver malignancy. Median FLR hypertrophy after ALPPS-1 was 54% (range, 6.7–133%) and median EBL during the ALPPS 1 and ALPPS 2 stages was 200 mL (range 0–1000) and 700 ml (range 100–4000), respectively. R0 resections were achieved in all patients (100%). Most complications occurred post ALPPS- 2 (n = 33/72, 45.8%), while overall 30-day mortality was 13.3%. After a median follow up of 7 months (range 3–60), recurrence rate was 18.9%. Disease-free survival ranged from 3 to 60 months with a median of 10 months and overall survival ranged from 3 to 60 months with a median of 11 months. ALPPS with the various technical modifications offers a reasonable chance of complete tumor resection among patients with initially unresectable primary liver tumors. Further advances in patient selection, surgical techniques and perioperative management are required to minimize complications rates. Large scale prospective trials are needed to validate the role of the technical modifications of ALPPS in the treatment of patients with primary liver malignancies in an individualized setting.